2006
DOI: 10.1103/physrevb.73.014517
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the magnetosuperconductorRuSr2Eu1.5Ce0.5Cu2

Abstract: has been explained in terms of a theory which combines the effects of weakening magnetic behavior and reducing carrier concentration in a phenomenological manner. The resulting theory is found to provide a good agreement with the observed value of T c .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
2
11
0
1
Order By: Relevance
“…A phenomenological theoretical approach to explain this competing behavior is underway. 12 In conclusion, it is shown that substitution of both Co and Mo at Ru-site in RuSr 2 Eu 1.5 Ce 0.5 Cu 2 O 10−δ system takes place iso-structurally in tetragonal structure (space group I4/mmm) with full solubility. With progressive Co substitution at Ru-site both T c (R = 0) and T dia c decrease monotonically and SC is not observed above 7.5% doping level.…”
Section: Resultsmentioning
confidence: 76%
“…A phenomenological theoretical approach to explain this competing behavior is underway. 12 In conclusion, it is shown that substitution of both Co and Mo at Ru-site in RuSr 2 Eu 1.5 Ce 0.5 Cu 2 O 10−δ system takes place iso-structurally in tetragonal structure (space group I4/mmm) with full solubility. With progressive Co substitution at Ru-site both T c (R = 0) and T dia c decrease monotonically and SC is not observed above 7.5% doping level.…”
Section: Resultsmentioning
confidence: 76%
“…이들 자성 초전도체의 구성은 일반적으로 RuSr2(R2-yCey)Cu2O10(Ru-1222) 및 RuSr2RCu2O10(Ru-1212) 로 나타낼 수 있으며, R 은 희토류 원소로서 Sm, Eu 및 Gd 의 경우만 상압에서 단 일상이 형성됨이 알려져 왔다 [4]. 특히 Ru-1222 계는 Ru-1212 계에 비해 강자성 특성이 크게 관측되어 [5] 그 원인을 파악하기 위해 많은 치환연구가 수행되어 왔 으며, (Ru1-xMx)Sr2(R2-yCey)Cu2O10((Ru,M)-1222) 조성에 대한 연구에서 M = Fe [6], Co [7], Nb [8,9], Mo [10], Sn [11], Sb [12] …”
Section: 서 론unclassified
“…It is possible to control relevant parameters that affect the superconducting properties of the sample by studying chemically altered compounds, with proper chemical substitutions, and thus it is possible to obtain a better understanding on the mechanisms of superconductivity. Specially, substitutions in the Ru site can be used to investigate superconductivity, for example, Mo [15], Co [16], Sn [17], Sb [18], and Pb [19] substitutions affect the carrier density in the CuO 2 planes. Nb substitution for Ru is more interesting because Nb is a nonmagnetic ion, and both Nb and Ru ions have valence close to 5 + , and changes in the carrier density should be smaller than in previous examples.…”
Section: Introductionmentioning
confidence: 99%